Telaah Terhadap Kitab Al-Luma’ Fī Asbāb Al-Wurūd Al-Hadīth Karya Imam Jalaluddin Al-Suyuthi - Hasyim, Muhammad Sulaiman; Zainnurrofiq, Muhammad; Faqih, Muhammad Abdurrohman (CENDEKIA: Jurnal Studi Keislaman, 2024)
This article wants to examine in depth and examine the book Al-Luma’ fī Asbāb al-Wurūd al-Hadīth by a famous scholar named Al-Hafidz Imam Jalaluddin al-Suyuthi.  In this paper, the author uses library research methods by referring to the main work of Imam Jalaluddin al-Suyuthi, namely the book Al-Luma’ fī Asbāb al-Wurūd al-Hadīth which is one of the books in the study of asbabul wurud hadith which is very phenomenal and is often used as a reference for looking for asbabul wurud from a hadith.  The results of this research show that the book Al-Luma’ fī Asbāb al-Wurūd al-Hadīth is a book of asbabul wurud hadith which has its own method and system in collecting and mentioning each hadith and its asbabul wurud.  The book Al-Luma’ fī Asbāb al-Wurūd al-Hadīth also refers to 35 reference sources and contains a lot of additional information regarding asbabul wurud hadith which is not found in other books.  This makes the existence of this book by Imam Jalaluddin al-Suyuthi greatly contribute to hadith scholarship, especially the study of asbabul wurud hadith.